Numerical investigation of RC beams strengthened with prestressed CFRP. Issue 3 (3rd July 2017) - Daugevičius, Mykolas
Abstract: Different strengthening technique was evaluated in order to investigate the effect of prestress. The analysed beams were strengthened with non-prestressed CFRP and prestressed CFRP at different loading levels. It has allowed a better understanding about strengthening effectiveness. Results obtained by finite element analysis were compared with experimental results obtained by other researchers. Phased nonlinear analysis was used to simulate the behaviour of the strengthened beams. Performed analysis showed that it is possible to use finite element analysis in order to investigate a real behaviour of the strengthened elements in real structure.